Indonesian Local Literary Rituals in Magical Realism - Suwandana, Engkin; Supratno, Haris; Suyatno; Suhartono (International Journal Linguistics of Sumatra and Malay, 2023)
This study aims to find magical realism in the Bantengan performance, find namely the irreducible elements, the phenomenal world, merging realms, the unsettling doubts, and disruptions of time, space, and identity at the Bantengan show. The method used to reveal these aspects is a qualitative method with an ethnographic approach. Theoretically, this research finds magical realism. Practically for researchers, this research is expected to broaden scientific horizons and can be used as a guide to carry out research, especially about traditions that develop in society. For the community, this research is expected to provide an overview of the actual Bantengan performance and provide knowledge to the public that the art of Bantengan contains the meaning of a performance that contains the value of magical realism. The results of this study: 1. The irreducible elements namely Cakepan in the art of bantengan are read as if telling the figure of a bull in the performance arena, furthermore it is used as advice and a medium for conveying messages to the public. 2. the phenomenal world, namely the movements in the Banteng symbolizing the life of the Banteng animal as an authoritative and strong base or forest animal, 3. merging realms, namely between types of religious magical beliefs and Islam there is a harmonious blend, as seen by the reading of prayers that derived from the verses of the Koran at the ceremony, 4. the unsettling doubts, namely the public's belief is still visible in the giving of offerings or offerings before holding a bantengan presentation, 5. disruptions of time, space and identity namely Bantengan and ndadi being one of the elements of the show that cannot be separated, so that it becomes a special attraction for the community.